Risk-based approach and quality of independent audit using structure equation modeling: Evidence from Vietnam - Le Thi Tam; Thi Mai Anh Nguyen; Van Quang Do; Thi Hai Chau Ngo (European Research on Management and Business Economics (ERMBE), 2022)
This study considers factors affecting to audit performance by risk-based approach (RBA) as well as audit quality in Vietnam. In addition, the study also examines the relationship between RBA and quality of independent audit firms. A descriptive survey research was adopted using both quantitative and qualitative methods. Qualitative research was conducted to consider the characteristics of RBA, and to identify items affecting to RBA application. A purposeful sampling method was used to select intentionally a target audience of 18 qualified experts. To examine influent factors, the study targeted 500 professional auditors but 355 returned the survey questionnaire. Performing data analysis by using structure equation modeling (SEM), the research findings revealed positive relationships between capacity of auditors, job pressure on auditors, the support of information technology, competitive ability of audit firms, audit fees, client's risks and the application of RBA, as well as quality of independent audits in Vietnam. Of which as supported by many previous studies, client's risks and information technology have the strongest relationship. On the other hand, RBA also positively and significantly affect to quality of independent audit firms. Finally, some recommendations were proposed based on the results of influent factors.
Keywords: D81; G32; M42; 650; Audit quality; Audit technology; Risk management; Vietnam